If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -13 = 2x + -5 Reorder the terms: -13 + 6x = 2x + -5 Reorder the terms: -13 + 6x = -5 + 2x Solving -13 + 6x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -13 + 6x + -2x = -5 + 2x + -2x Combine like terms: 6x + -2x = 4x -13 + 4x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 -13 + 4x = -5 + 0 -13 + 4x = -5 Add '13' to each side of the equation. -13 + 13 + 4x = -5 + 13 Combine like terms: -13 + 13 = 0 0 + 4x = -5 + 13 4x = -5 + 13 Combine like terms: -5 + 13 = 8 4x = 8 Divide each side by '4'. x = 2 Simplifying x = 2
| 3x-18=x+10 | | w^2+16=8w | | 2x+5x=3.5 | | 10y+2=x-6 | | (2b)2= | | [5.6]= | | 3u^2-11u=4 | | [-2/3]= | | 5r(4r-5)=0 | | [-9]= | | 12x-29=79 | | 10x+1=9x-x+3 | | [8]= | | 2ab*4b= | | 7-5z=6z-26 | | 3z^2-3z-6=0 | | 13x+7=215 | | 28m^4-14m^3+7m^2= | | 4x-9=3.5x-9 | | x^2+4y^2=16 | | 12c^2d^3-18cd^2= | | 3x-1=1-3x | | 74-3x=33x+22 | | 6x-7=5x+15 | | 2x+1=2x-1 | | 6x^3-2x^2= | | x^2-16y^2+4x+96y-124=0 | | x+6=x | | 2y+1y=3y+2 | | 3+5t-2=7t+19-4t | | 8x-14=58 | | -3x-2y=-10 |